The effect of eradaicating helicobacter pylori infection on intragastric pH and serum gastrin concentrations - İrfan SOYKAN and Ali ÖZDEN and Yusuf UZUN and Hülya ÇETİNKAYA and Ali Reşit BEYLER and Kadir BAHAR and Nihat SİPAHİ and; n UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-